Financial literacy and financial education on financial behavior in college students: the mediating effect on investment motivation - Haqiqi, Teuku Muhammad; Hanifa, Riri; Bela, Iglima Anisa; Erdiyanto, Rico; Paiza, Ela (Institute of Computer Science (IOCS), 2024)
This study aims to test empirically how the influence of financial literacy, financial education on financial behavior. Then to see how much that all influence financial behavior mediates by investment motivation at students. This study employs a quantitative research design and a population of 6,350 students. The sampling technique was proportional stratified random, and the Slovin formula was used to determine the requisite number of respondents, which was established to be 376 students. The findings in this study are that all variables have a significant and positive relationship in accordance with the hypothesis